Clinical Pharmacogenetics Implementation Consortium Guidelines for Thiopurine Methyltransferase Genotype and Thiopurine Dosing: 2013 Update. Issue 4 (17th January 2013) - Relling, M V; Gardner, E E; Sandborn, W J; Schmiegelow, K; Pui, C‐H; Yee, S W; Stein, C M; Carrillo, M; Evans, W E; Hicks, J K; Schwab, M; Klein, T E
<x xml:space="preserve">Abstract</x> The Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for Thiopurine Methyltransferase Genotype and Thiopurine Dosing was originally published in March 2011. We reviewed recent literature and concluded that although relevant new evidence has been generated, none of the evidence would change the primary dosing recommendations in the original guideline; therefore, the original publication remains clinically current. Up‐to‐date information on thiopurine methyltransferase (TPMT) gene alleles and nomenclature can be found at PharmGKB (http://www.pharmgkb.org). Clinical Pharmacology & Therapeutics (2013); 93 4, 324–325. doi:10.1038/clpt.2013.4